2010
DOI: 10.1038/mt.2009.207
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Delivery of Synthetic MicroRNA-16 Inhibits the Growth of Metastatic Prostate Tumors via Downregulation of Multiple Cell-cycle Genes

Abstract: Recent reports have linked the expression of specific microRNAs (miRNAs) with tumorigenesis and metastasis. Here, we show that microRNA (miR)-16, which is expressed at lower levels in prostate cancer cells, affects the proliferation of human prostate cancer cell lines both in vitro and in vivo. Transient transfection with synthetic miR-16 significantly reduced cell proliferation of 22Rv1, Du145, PPC-1, and PC-3M-luc cells. A prostate cancer xenograft model revealed that atelocollagen could efficiently deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
257
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(265 citation statements)
references
References 27 publications
3
257
0
5
Order By: Relevance
“…In addition, miR-16 was shown to inhibit bone metastasis in a mouse prostate cancer xenograft model. 68 MiR-146a was shown to target ROCK1 in androgen-independent PC3 cells; overexpression of miR-146a led to reduced proliferation and invasion, and impaired adhesion to a monolayer of human bone marrow endothelial cells. 69 Finally, multiple studies have shown inhibitory effects from miR-145 on prostate cancer bone metastasis.…”
Section: Tumor-intrinsic Mirna Regulation Of Bone Metastasismentioning
confidence: 99%
“…In addition, miR-16 was shown to inhibit bone metastasis in a mouse prostate cancer xenograft model. 68 MiR-146a was shown to target ROCK1 in androgen-independent PC3 cells; overexpression of miR-146a led to reduced proliferation and invasion, and impaired adhesion to a monolayer of human bone marrow endothelial cells. 69 Finally, multiple studies have shown inhibitory effects from miR-145 on prostate cancer bone metastasis.…”
Section: Tumor-intrinsic Mirna Regulation Of Bone Metastasismentioning
confidence: 99%
“…LNA directed against miR-21 reduced tumor growth in vivo [110] , which suggests a therapeutic role for anti-miR-21 in treating cancers. In addition, miR-16, which is frequently deleted and/ or down-regulated in human cancers, significantly inhibits prostate tumor growth in vivo when delivered by atelocollagen via tail vein injection [111] . These results indicate that the delivery of miR-16 could be used to treat patients with advanced prostate cancer.…”
Section: Implications Of Cell Cycle-related Mirnas In Anti-cancer Thementioning
confidence: 99%
“…Fifty micrograms of double-strand mature mmu-miR-29a (miR-29a) or nonspecific oligonucleotide (negative control for miR-29a: NC miRNA) (Bonac, Fukuoka, Japan) was mixed with 200 ”l of atelocollagen (Atelo gene; KOKEN, Tokyo, Japan) and injected via the tail vein every 3 days. 36 MiRNA was administrated two times in mice treated for 1 week and four times in mice treated for 2 weeks. Thus, mice for each fibrotic model were now spread over eight groups: observed without any treatment (1 week observation/2 weeks observation), administrated only atelocollagen, a vehicle for nucleotides (1 week vehicle/2 weeks vehicle), administrated NC miRNA (1 week NC miRNA/2 weeks NC miRNA), or administrated miR-29a (1 week miR-29a/2 weeks miR29a) (Figure 2a).…”
Section: Administration Of Mir-29a In Vivomentioning
confidence: 99%